Ozone catalyzation modulated by oxygen vacancies over Co/Mg loading on biochar derived from Chlorella pyrenoidosa for wastewater purification - Wei, Xingyue; Zhang, Hanmin; Cao, MengBo (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
[Display omitted] •One-step pyrolysis prepared Co/Mg dispersions on NPC derived from Chlorella.•0.3Co9S8/MgO-NPC was proved high efficiency in catalyzing ozone for IBU removal.•·OH and *Oad were the main active species in 0.3Co9S8/MgO-NPC HCO process.•Abundant oxygen vacancies, Co2+ and M−O- act as active sites for ozone activation.•The coupling of Co/Mg with NPC improves the stability of the 0.3Co9S8/MgO-NPC. In this study, a series of biochar-based materials (nCo9S8/MgO-NPC) doped with different Co and Mg mass ratios were successfully prepared through a one-step pyrolysis method using Co(NO3)2·6H2O, MgSO4·7H2O and N, P-rich Chlorella pyrenoidosa (CP) as raw materials for the degradation of ibuprofen (IBU) by heterogeneous catalytic ozonation (HCO) process. The nCo9S8/MgO-NPC catalysts exhibited superior HCO activity compared with NPC, Co-NPC, MgO-NPC and 0.3Co9S8/MgO. It was also found that the HCO activity gradually increased as the Co/Mg mass ratio decreased, and 0.3Co9S8/MgO-NPC exhibited the highest HCO activity, with a corresponding reaction rate constant of 0.224 min−1. The 0.3Co9S8/MgO-NPC/O3 system also exhibited better catalytic stability after four cycles, mitigating the hydration of MgO and Co ion leaching. The IBU removal was mainly attributed to the surface adsorbed atomic oxygen (*Oad) and hydroxyl radicals (·OH). Deprotonation of surface hydroxyl groups, oxygen vacancies (OVs) and the redox reactions of Co2+ were confirmed to be the active sites promoting the decomposition of ozone by using techniques such as X-ray Photoelectron Spectroscopy (XPS) and Electron Paramagnetic Resonance (EPR). The degradation pathway of IBU was deduced and the toxicity of the intermediates was evaluated. 0.3Co9S8/MgO-NPC displayed notable anti-interference to various complex water quality, including inorganic anions, humic acid (HA) and so on. This study provides valuable insights for the design of efficient MgO-based catalysts for catalytic ozonation in environmental management and industrial applications.